Hen Egg‐White Lysozyme Crystallisation: Protein Stacking and Structure Stability Enhanced by a Tellurium(VI)‐Centred Polyoxotungstate. Issue 2 (17th December 2014) - Bijelic, Aleksandar; Molitor, Christian; Mauracher, Stephan G.; Al‐Oweini, Rami; Kortz, Ulrich; Rompel, Annette
Abstract As synchrotron radiation becomes more intense, detectors become faster and structure‐solving software becomes more elaborate, obtaining single crystals suitable for data collection is now the bottleneck in macromolecular crystallography. Hence, there is a need for novel and advanced crystallisation agents with the ability to crystallise proteins that are otherwise challenging. Here, an Anderson–Evans‐type polyoxometalate (POM), specifically Na6[TeW6O24]⋅22 H2O (TEW), is employed as a crystallisation additive. Its effects on protein crystallisation are demonstrated with hen egg‐white lysozyme (HEWL), which co‐crystallises with TEW in the vicinity (or within) the liquid–liquid phase separation (LLPS) region. The X‐ray structure (PDB ID: 4PHI) determination revealed that TEW molecules are part of the crystal lattice, thus demonstrating specific binding to HEWL with electrostatic interactions and hydrogen bonds. The negatively charged TEW polyoxotungstate binds to sites with a positive electrostatic potential located between two (or more) symmetry‐related protein chains. Thus, TEW facilitates the formation of protein–protein interfaces of otherwise repulsive surfaces, and thereby the realisation of a stable crystal lattice. In addition to retaining the isomorphicity of the protein structure, the anomalous scattering of the POMs was used for macromolecular phasing. The results suggest that hexatungstotellurate(VI) has great potential as a crystallisation additive to promote both protein crystallisation and structure elucidation.